Cluster Analysis of Ranunculus Species - SURANTO SURANTO (Society for Indonesian Biodiversity, 2002)
The aim of the experiment was to examine whether the morphological characters of eleven species of Ranunculuscollected from a number of populations were in agreement with the genetic data (isozyme). The method used in this study was polyacrilamide gel electrophoresis using peroxides, estarase, malate dehydrogenase, and acid phosphatase enzymes. The results showed that cluster analysis based on isozyme data have given a good support to classification of eleven species based on morphological groups. This study concluded that in certain species each morphological variation was profit to be genetically based.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey Words: Ranunculus, isozyme